A Challenging Diagnosis of Acute Myeloid Leukemia with Myelodysplasia Related Changes in the Setting of Ayurvedic Supplements and B12 Deficiency. (28th October 2020) - Goff, R; Levyq, R
Abstract: Introduction/Objective: Bone marrow findings of myelodysplastic changes can be associated with vitamin or mineral deficiencies (B12, folic acid or copper), infections, inflammatory disorders, exposure to toxins, heavy metals, zinc excess, recent radio- or chemotherapy, or myeloid neoplasms including myelodysplasia (MDS) and acute myeloid leukemia (AML). We present a case of a 32 year old Indian woman who presented with fatigue and weakness. She has a history of vitamin B12 deficiency and has been taking Ayurvedic supplements. This clinical history is very important because studies have shown that vitamin B12 deficiency has led to incorrect diagnoses of AML and/or MDS. Additionally, Ayurvedic supplements can contain a variety of heavy metals which can contribute to myelodysplastic changes. Results: A complete blood count and peripheral smear analysis showed pancytopenia with rare blasts. A bone marrow core biopsy with ancillary testing was performed to evaluate for a hematologic malignancy. Vitamin B12 testing and heavy metal analysis was necessary to reach a final diagnosis. Flow cytometric analysis of the marrow identified 19.5% CD34 positive myeloblasts. The aspirate and core are hypercellular with increased blasts (17% on aspirate and 20-25% on core biopsy) with trilineage dyspoiesis. AML panel by fluorescence in situ hybridization showed no abnormalities. Heavy metal analysis shows no increase in lead, cadmium, mercury and arsenic levels. Recent vitamin B12 tests show results within normal range secondary to successful replacement. Ultimately, chromosome analysis identifies t(3;12)(q26, p13) involving ETV6/MECOM characteristic of a very poor prognosis in MDS or AML. Molecular AML panel identified BCOR and PTPN11 gene mutations which are associated with more aggressive disease and a poor prognosis in myeloid neoplasms. Conclusion: This case had multiple possible causes of myelodysplastic changes and it was necessary to exclude these factors before yielding the final diagnosis of Acute Myeloid Leukemia with myelodysplastic related changes which demonstrated a rare translocation t(3;12) ETV6/MECOM which has a poor prognosis.